On the nature of pleural involvement in necrotizing pneumonia: A report of two cases of life threatening late complications. Issue 3 (23rd November 2013) - Demirel, Nadir; Quizon, Annabelle; Beltetón De Leon, Edgar Leonel; Reiter, Joel; Colin, Andrew A.
Summary Suppurative complications of pneumonia such as empyema, lung abscess, pyopneumothorax, and necrotizing pneumonia (NP) are uncommon in children. Over the last decade an increasing incidence of NP has been reported. Streptococcus pneumoniae continues to be the predominant causative organism of NP, and while sporadic cases were reported prior to routine administration of heptavalent pneumococcal vaccine, a marked increase in NP appears to relate to replacement pneumococcal strains. Pleural involvement is almost universal in NP, and the course of pleural disease often determines its duration and outcome, particularly as it relates to complication of bronchopleural fistula. Cavities are formed in NP within the lung parenchyma and in the pleural space as the fibrosing pleural process organizes. The similarity of the radiologic appearance of parenchymal and pleural space cavities often makes the differentiation of pneumatocele versus residua of loculated pneumothorax challenging. The prevailing perception from most reports on childhood NP is of a favorable outcome with conservative approach. We report two pediatric cases with pneumonia who presented with prolonged fever despite antibiotic treatment, eventually diagnosed with NP. After stabilization on prolonged IV antibiotics, and weeks after discharge, they presented with unexpected acute respiratory failure due to a life‐threatening tension air collection. In this article we discuss the nature of NP, its typical presentation, benign course and outcome, albeit its potential to cause serious late complications in the light of our recent experiences. Increasing awareness of such complications will result in more careful follow‐up and in providing appropriate recommendations to parents of patients recovering from NP. Pediatr Pulmonol. 2014; 49:E90–E95. © 2013 Wiley Periodicals, Inc.